Succeeding with interventions for Asperger syndrome adolescents : a guide to communication and socialisation in interaction therapy - Harpur, John, 1958- (Jessica Kingsley Publishers, 2006)
This vital new book presents effective strategies to tackle the specific difficulties in social interaction and communication that are experienced by adolescents with Asperger Syndrome (AS). Focusing on the development of interaction skills through teaching social competence, the authors explain how to design an effective social skills intervention programme whose primary objective is successful peer interaction. They describe the methodology, philosophy and science underpinning their approach and include a template for a sample course currently administered over six months. Guidance is given.